2017
DOI: 10.1039/c7sc01070b
|View full text |Cite
|
Sign up to set email alerts
|

Photochemically active DNA-intercalating ruthenium and related complexes – insights by combining crystallography and transient spectroscopy

Abstract: Recent research on the study of the interaction of ruthenium polypyridyl compounds and defined sequence nucleic acids is reviewed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
76
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 65 publications
(80 citation statements)
references
References 137 publications
3
76
0
1
Order By: Relevance
“…These spectra can then be directly compared to the TA and TRIR spectra obtained for photoexcited [Ru(TAP)2(dppz)] 2+ , which when bound to guanine-containing DNA lead to photooxidation of guanine. [25][26][27][28][29][30] The yield of this photo-induced electron transfer has been shown to depend on both the enantiomer and the sequence of the DNA. 25,[27][28][29][30] One of the highest yielding system so far examined is that of the Λ-enantiomer intercalated in double-stranded d(G5C5).…”
Section: Dft Calculations On the Electronic And Vibrational Absorptiomentioning
confidence: 99%
See 2 more Smart Citations
“…These spectra can then be directly compared to the TA and TRIR spectra obtained for photoexcited [Ru(TAP)2(dppz)] 2+ , which when bound to guanine-containing DNA lead to photooxidation of guanine. [25][26][27][28][29][30] The yield of this photo-induced electron transfer has been shown to depend on both the enantiomer and the sequence of the DNA. 25,[27][28][29][30] One of the highest yielding system so far examined is that of the Λ-enantiomer intercalated in double-stranded d(G5C5).…”
Section: Dft Calculations On the Electronic And Vibrational Absorptiomentioning
confidence: 99%
“…[25][26][27][28][29][30] The yield of this photo-induced electron transfer has been shown to depend on both the enantiomer and the sequence of the DNA. 25,[27][28][29][30] One of the highest yielding system so far examined is that of the Λ-enantiomer intercalated in double-stranded d(G5C5). 30 The TA and TRIR spectra of this system after the electron transfer process is complete are shown in Figure 9 As noted in the Introduction, it has been reported that the excited state of [Ru(TAP)2(dppz)] 2+ is efficiently quenched by 5′-GMP and nanosecond flash photolysis showed the formation of transient species expected to be [Ru(TAP)(TAPH)(dppz)] 2+ and the guanine radical (equation 4).…”
Section: Dft Calculations On the Electronic And Vibrational Absorptiomentioning
confidence: 99%
See 1 more Smart Citation
“…[28] More recently theses tructural observations have been used to interpret longstanding discussions in the literature about observations of multiple luminescence lifetimes even in apparently homogeneous Ru-DNA model systems. [29] The realisation that the typical binding mode fort hese complexes is angled intercalation prompted the investigation of the effect of asymmetrics ubstitution of the distal ring of the dppz ligand [30] (positions 10-13 in Figure 1b).…”
Section: Introductionmentioning
confidence: 99%
“…However, dose limiting side effects including neurotoxicity and nephrotoxicity and the development of both acquired and inherently resistant cancers continue to be an ongoing issue in its treatment success. As such, recent research activity has focused on the rational design of metallo-agents including ruthenium [1][2][3][4][5], iron [6,7], gold [8][9][10] and copper [11][12][13][14][15][16][17][18][19] with alternative mode of action to the mono-nuclear cis-[PtX 2 (amine) 2 ] chemotype (X = leaving group, amine = neutral or carrier group) shared by cisplatin and its derivatives [20].…”
Section: Introductionmentioning
confidence: 99%